2019
DOI: 10.3390/su11040954
|View full text |Cite
|
Sign up to set email alerts
|

Developing Sustainable Healthcare Systems in Developing Countries: Examining the Role of Barriers, Enablers and Drivers on Knowledge Management Adoption

Abstract: Knowledge management (KM) adoption is crucial to integrating sustainable development within the healthcare sector. Different barriers, enablers, and drivers affect KM adoption. Identifying these barriers, enablers, and drivers and their role in KM adoption is the core of successful KM adoption. However, there is scarcity of studies applying quantitative models and combing barriers, enablers and drivers to check their effect on KM adoption, especially form a developing country’s perspective such as Pakistan. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 117 publications
2
23
0
Order By: Relevance
“…This is especially important considering the fast-economic growth of the healthcare industry in emerging countries such as, among others, India, China and Brazil. Recent research ( Karamat et al, 2019 ) confirms how the use and management of knowledge resources is strategic to promote learning and innovation in developing countries.…”
Section: Discussionmentioning
confidence: 87%
“…This is especially important considering the fast-economic growth of the healthcare industry in emerging countries such as, among others, India, China and Brazil. Recent research ( Karamat et al, 2019 ) confirms how the use and management of knowledge resources is strategic to promote learning and innovation in developing countries.…”
Section: Discussionmentioning
confidence: 87%
“…There are different multi-criteria decision-making (MCDM) approaches such as analytical network process ANP, graph theory, DEMATEL, Best Worst Method, and Interpretive Structural Modeling ISM approach. [70][71][72][73][74][75][76][77][78][79][80][81][82][83] However, these approaches are not suitable as compare with AHP-TOPSIS [84] for MCDM problems including experts' opinion which purpose is to examine the appropriate alternative specified in a set of criteria (as shown in Table 3). Therefore, this study incorporated FAHP and TOPSIS techniques because FAHP helps to remove the uncertainty, ambiguousness, and complex problems in MCDM valuation criteria through the utilization of interval numbers.…”
Section: The Literature On the Proposed Methodologymentioning
confidence: 99%
“…These global perspectives are also reflected in leadership in Pakistan where it has been shown that through knowledge management, transformational leadership styles positively predict rational decision-making and organizational learning and organizational performance [34][35][36]. As shown in the health-care sector of developing countries, lack of support from senior management, insufficient strategic planning, and inadequate organizational structures continue to impede effective knowledge management [37,38]. Tellingly, knowledge sharing motivation among employees is insufficient to overcome the barriers of inadequate organizational culture or leadership [39].…”
Section: Public Sector Leadershipmentioning
confidence: 99%